Prophetic Approvals in Practice: A Study of Taqreeri Ahadith on Worship in Sahih Bukhari: صحیح بخاری میں عبادات سے متعلق تقریر ی احادیث کا مطالعہ - Ahmed, Dr. Altaf; Sultana, Dr. Irum; Malik, Saira Jabeen (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Prophetic Approvals in Practice: A Study of Taqreeri Ahadith on Worship in Sahih Bukhari. This study explores the category of Taqreeri Hadith (Prophetic tacit approvals) related to acts of worship (ʿIbādāt) as documented in Sahih Bukhari. These Hadiths represent a unique and authoritative source within the Sunnah, where the Prophet Muhammad (PBUH) neither verbally instructed nor actively participated in an action, but his silence in the face of a companion’s deed is understood as an implicit endorsement. This research aims to identify, analyze, and interpret such narrations in the domain of worship, including prayer, fasting, purification, and other ritual acts. By doing so, it highlights the methodological importance of tacit approvals in deriving legal and theological principles in Islamic jurisprudence. The study also examines how these Hadiths have been utilized by classical scholars to establish normative rulings and the extent to which they shape Islamic legal discourse. Ultimately, this research underlines the epistemological value of Taqreeri Hadith in understanding the Prophet’s role as a divine guide beyond verbal and practical Sunnah.